2012
DOI: 10.1093/nar/gks779
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic binding of Topoisomerase I impacts on the transcription of Bmal1 and circadian period

Abstract: The Bmal1 gene is essential for the circadian system, and its promoter has a unique open chromatin structure. We examined the mechanism of topoisomerase I (Top1) to understand the role of the unique chromatin structure in Bmal1 gene regulation. Camptothecin, a Top1 inhibitor, and Top1 small interfering RNA (siRNA) enhanced Baml1 transcription and lengthened its circadian period. Top1 is located at an intermediate region between two ROREs that are critical cis-elements of circadian transcription and the profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…This TOP1 association was less pronounced in the presence of CPT (Figure 6B). TOP1 participates in re-shaping the chromatin structure of its target genes and shows enrichment at chromatin marks such as H3K4me3 [42,43]. As inflammatory cytokines subsequently also lead to changes in histone modifications at inflammatory genes including IL8 [39], it was interesting to test whether CPT might also affect these events.…”
Section: Resultsmentioning
confidence: 99%
“…This TOP1 association was less pronounced in the presence of CPT (Figure 6B). TOP1 participates in re-shaping the chromatin structure of its target genes and shows enrichment at chromatin marks such as H3K4me3 [42,43]. As inflammatory cytokines subsequently also lead to changes in histone modifications at inflammatory genes including IL8 [39], it was interesting to test whether CPT might also affect these events.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important findings was that altering the DNA configuration of the Bmal1 promoter causes the epigenetic regulation of Bmal1 circadian transcription [86]. Topoisomerase I (TOP1) is located at an intermediate region between two ROREs that are critical cis-elements of circadian transcription, which is required for transcriptional suppression in cooperation with the distal RORE.…”
Section: Assays Of Bmal1 Transcription Modulatorsmentioning
confidence: 99%
“…Topoisomerases, including type I (TOPI) and type II (TOPII), are key enzymes for DNA replication, transcription, recombination and chromatin remodeling [65]. In a recent study, it was shown that TOPI suppressed Bmal1 transcription via binding to an intermediate region between the two RORE elements in the promoter.…”
Section: Targets Of Small-molecule Clock Modulatorsmentioning
confidence: 99%
“…In a recent study, it was shown that TOPI suppressed Bmal1 transcription via binding to an intermediate region between the two RORE elements in the promoter. Camptothecin, a TOPI inhibitor, enhanced Bmal1 transcription and lengthened the circadian period [65]. In addition, the TOPI inhibitor harmine also lengthened the circadian period by enhancing the trans-activating function of RORα in vitro and in vivo [66, 67].…”
Section: Targets Of Small-molecule Clock Modulatorsmentioning
confidence: 99%